Determination of the pKa of hydroxy-benzophenones in ethanol-water mixtures. Solvent effects - Castro, Gabriela Tatiana (2003)
Benzophenones are compounds of great importance due to their biological and physicochemical properties. The purpose of the present work was to determine by a UV-Visible spectroscopic method, the pKa of 4(OH)benzophenone, 2(OH)benzophenone and 2(OH),4(CH3O)benzophenone in ethanol-water solutions, varying solvent permittivity in the interval 61-72, at constant ionic strength (0.050) and temperature (25.0 ± 0.1 °C). The pKa values of the compounds increase when the polarity-polarizability and solvation abilities of the reaction medium decrease. Correlations were established between the pKa values and solvation parameters of the solvents, such as the relative permittivity, the α parameter of Taft the solvatochromatic polarity-polarizability parameter π* and the parameter Acity. Excellent linear equations were obtained from which pKa values were determines in pure water. The structures of all the chemical species involved in the acid-base dissociation equilibria studied were calculated at the RHF/6-31G(d) level of theory, in ethanol and water. Considering the theoretical pKa values, the conclusions obtained match our experimental determinations.